A mainstream anammox fixed-film membrane bioreactor with novel sandwich-structured carriers for fast start-up, effective sludge retention and membrane fouling mitigation - Zhang, Meng (2022)
Novel sandwich-structured carriers were developed for fast immobilizing anammox sludge, with which a fixed-film membrane bioreactor was further established for treating municipal wastewater. Results showed that fast start-up of the fixed-film reactor with anammox bacteria could be achieved without lag phase, indicated by the respective nitrogen removal efficiency and rate of 70.58 ± 0.66% and 0.12 g N/(L·d). Meanwhile, low membrane fouling 0.0017 bar/hour was also observed. The activity of anammox sludge fixed in the novel carriers gradually stabilized at the level of 6.59 mg N/(g VSS·h), while Candidatus Kuenenia as the dominant anammox bacteria were enriched from the initial abundance of 15.16% to 39.12% after a long-term operation. Consequently, it was demonstrated that the sandwich-structured carriers developed in this study could offer a promising alternative for fast immobilization and start-up of mainstream anammox process.